2011
DOI: 10.1111/j.1365-294x.2011.05359.x
|View full text |Cite
|
Sign up to set email alerts
|

Is diversification history of maize influencing selection of soil bacteria by roots?

Abstract: A wide range of plant lines has been propagated by farmers during crop selection and dissemination, but consequences of this crop diversification on plant-microbe interactions have been neglected. Our hypothesis was that crop evolutionary history shaped the way the resulting lines interact with soil bacteria in their rhizospheres. Here, the significance of maize diversification as a factor influencing selection of soil bacteria by seedling roots was assessed by comparing rhizobacterial community composition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 71 publications
5
90
1
3
Order By: Relevance
“…Conversely, EMBRAPA rhizospheres may have acquired their OTU 212 from soils as only 0.4 % of the conseq in sterile sand rhizospheres belonged to that OTU, compared to 35 and 39 % for rhizospheres from subsoil and terra preta grown plants. The apparent dominance of Burkholderia species that we have observed in juvenile maize plants is not unprecedented: Burkholderia have been reported to be the most abundant genera of bacteria in rhizospheres of turf grasses (Vandenkoornhuyse et al 2007), in rhizospheres of maize grown under field conditions (Bouffaud et al 2012;Peiffer et al 2013), in hybrid maize seeds in China (Liu et al 2013b), in moss sporophytes and gametophytes (Bragina et al 2013) and in mimosa roots (Elliott et al 2009). More than one species of Burkholderia matches OTU 212, highlighting a general problem with relying only on 16S data to predict specific taxonomy, ecology or behaviour of bacteria.…”
Section: Abundant and Conserved Otus In The Rhizospherementioning
confidence: 88%
See 1 more Smart Citation
“…Conversely, EMBRAPA rhizospheres may have acquired their OTU 212 from soils as only 0.4 % of the conseq in sterile sand rhizospheres belonged to that OTU, compared to 35 and 39 % for rhizospheres from subsoil and terra preta grown plants. The apparent dominance of Burkholderia species that we have observed in juvenile maize plants is not unprecedented: Burkholderia have been reported to be the most abundant genera of bacteria in rhizospheres of turf grasses (Vandenkoornhuyse et al 2007), in rhizospheres of maize grown under field conditions (Bouffaud et al 2012;Peiffer et al 2013), in hybrid maize seeds in China (Liu et al 2013b), in moss sporophytes and gametophytes (Bragina et al 2013) and in mimosa roots (Elliott et al 2009). More than one species of Burkholderia matches OTU 212, highlighting a general problem with relying only on 16S data to predict specific taxonomy, ecology or behaviour of bacteria.…”
Section: Abundant and Conserved Otus In The Rhizospherementioning
confidence: 88%
“…The advent of sensitive molecular fingerprinting and affordable next generation sequencing technologies has sparked a renaissance in rhizosphere research, with many new studies concerning the bacterial diversity present in maize rhizospheres (Bakker et al 2015;Bouffaud et al 2012;Castellanos et al 2009;Dalmastri et al 1999;Peiffer and Ley 2013;Peiffer et al 2013), Arabidopsis rhizospheres (Bulgarelli et al 2012;Lundberg et al 2012;Micallef et al 2009) and the rhizospheres of other important plant species (Costa et al 2006;Edwards et al 2015;Garbeva et al 2008;Germida and Siciliano 2001;Inceoglu et al 2010;van Overbeek and van Elsas 2008;Weinert et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Soil environment and plant genotype also shape the microbiota of the rhizosphere of maize, although soil environment seems to be the most crucial factor, as samples across different locations in the USA have a more pronounced effect than samples of 27 different maize genotypes (Peiffer et al 2013). Nevertheless, plant genotype is an essential factor as demonstrated for rhizosphere bacterial communities in maize (Bouffaud et al 2012), methanogenic archaeal communities in rice (Conrad et al 2008), and methanotrophic bacterial communities in rice (Lüke et al 2011). The present study extends these results to two different plant species, maize and rice, which exhibited completely different ectoand endorhizosphere communities although they were grown in the same soil.…”
Section: Discussionmentioning
confidence: 99%
“…Deltaproteobacteria typically comprise bacteria with anaerobic metabolism (often obligatorily), such as iron reducers, sulfate reducers and syntrophic fermenting bacteria. Among the Alphaproteobacteria it is apparently the obligately aerobic genus Burkholderia that colonizes maize roots (Bouffaud et al 2012;Peiffer et al 2013), and also the aerobic methanotrophs, such as Methylocystis. However, methanotrophs were not among the 100 most common OTUs.…”
Section: Discussionmentioning
confidence: 99%
“…The plant, in turn, cultivates its microbiome by adjusting the soil pH, reducing competition for beneficial microbes, and providing an energy source, mostly in the form of carbon-rich rhizodeposits (2). Microbial community structure in the phyllosphere and rhizosphere often differ across plant species (7), as well as among genotypes within a single species (8,9). Recent work with model systems (Arabidopsis thaliana cultivated under controlled conditions in natural soils) indicated that the host genotype has a small but measurable effect on the microbes inhabiting the endophyte compartment of the root (10,11).…”
mentioning
confidence: 99%